Evaluation of Stilt Houses in Lebong Regency Against Earthquakes, Incorporating Ground Response and Structural Dynamics Analysis - Muhammad Wildan Al-Farizi; Lindung Zalbuin Mase; Hardiansyah Hardiansyah; Rena Misliniyati; Fepy Supriani; Salisa Chaiyaput (Journal Innovation of Civil Engineering (JICE), 2024)
Lebong Regency, located in Bengkulu Province, Indonesia, is in an earthquake-prone zone due to its proximity to the Ketahun Segment, part of an active fault system in the region. This condition makes the area highly vulnerable to seismic activity. The purpose of this research is to analyze the performance of stilt houses in Lebong Regency using an integrated methodology comprising ground response analysis and structural dynamics analysis to assess the potential effects of earthquakes. Site characterisation was undertaken to generate geological data in the area of study, marking the first stage of the study. The analysis proceeded with ground-shaking analysis to determine the characteristics of ground motion, including critical parameters such as the maximum ground acceleration (PGA), spectral response acceleration, and amplification factors. The next step was to simulate the propagation of earthquake waves to determine the structural behavior of buildings under earthquake shocks. The analysis results show that the stilt houses will have sufficient structural resistance under earthquake loading before and after the earthquake. All wooden structural components satisfy design requirements and strength checks as per the relevant design requirements. Keywords: Earthquake; Ground Response; Stilt Houses; Structural Dynamics Analysis.
Keywords: Geotechnical and construction materials studies; Cultural and Educational Studies; Earthquake and Tsunami Effects